Seismic response control of bridges with nonlinear tuned vibration absorbers. (December 2021) - Elias, Said; Rupakhety, Rajesh; De Domenico, Dario; Olafsson, Simon
Abstract: The paper investigates seismic response control of bridges with nonlinear tuned vibration absorbers (n-TVAs). A three-span continuous bridge is used as case study. The n-TVAs are designed to act in both longitudinal and transverse directions of the bridge. The n-TVAs are modelled as inelastic springs with bilinear hysteretic behavior. A simple and effective method to design the parameters of the n-TVAs for controlling structural displacement is presented. The performance of the proposed n-TVAs is compared with the optimum linear TVAs (o-TVAs) and elasto-plastic bilinear TVAs (bn-TVAs). The results show that the n-TVAs are at least as effective as o-TVAs in controlling structural response. Because the n-TVAs do not require additional dashpots like the o-TVAs, they provide a more economical solution. It is observed that although effective in controlling structural response, their stroke is of the same order as that of o-TVAs. Addition of a viscous dashpot to the device is found to reduce their stroke, although accompanied by an inherent detrimental effect on the structural control performance.